Incorporation of Platinum and Gold Partially Reduced Graphene Oxide into Polymer Electrolyte Membrane Fuel Cells for Increased Output Power and Carbon Monoxide Tolerance. Issue 20 (1st April 2016) - Isseroff, Rebecca; Blackburn, Lee; Kang, Jaymo; Li, Hongfei; Gentleman, Molly; Rafailovich, Miriam
ABSTRACT: The Polymer Electrolyte Membrane Fuel Cells (PEMFCs) platinum catalyst's susceptibility to poisoning by carbon monoxide (CO) reduces its output power. In an effort to diminish poisoning, gold and platinum nanoparticles were incorporated onto partially reduced graphene oxide (Au/Pt-prGO) sheets to reduce both nanoparticle aggregation and the amount of precious metal needed. Applying this material onto the electrodes and Nafion membrane of a PEMFC was hypothesized to increase CO tolerance as well as power output. Aliquots of graphene oxide (GO) were functionalized with platinum and/or gold nanoparticles using a simple desktop synthesis at room temperature. Partial reduction with NaBH4 maintained hydrophilic solubility. Test solutions applied to electrodes and to electrodes + Nafion membrane were first tested in a PEM fuel cell with a pure H2 gas feed and then repeated with a H2 gas feed containing 1000 ppm of CO. Test arrangements averaged doubling the output power of the poisoned control, with the most effective yielding an output power ∼250% that of the poisoned control. Additionally, each system's poisoned output power (PP ) was compared to its highest possible output power (PM ), with the most effective setup showing no reduction in output power, even with a H2 gas feed containing 1000 ppm of CO. Thus, this offers promise of a simple, cost-effective method of both improving PEMFC power output while reducing or even eliminating CO poisoning at room temperature.